Energy Recovery of Shrub Species as a Path to Reduce the Risk of Occurrence of Rural Fires: A Case Study in Serra da Estrela Natural Park (Portugal) - Nunes, Leonel (2022)
The accumulation of biomass fuels resulting from the growth of heliophilous shrubs and small tree species at the edge of forests and on scrub and pasture lands contributes to the increased risk of rural fires in Mediterranean climate regions. This situation has been managed with a set of legislative measures launched with the objective of promoting cleaning and the control of these species. Areas of scrub and pasture already constitute the largest part of the annually burnt area in Portugal, resulting in high-intensity fires. In the present study, shrubs and small tree species were characterized in the laboratory. Thermogravimetric, chemical and calorimetric analyses for the evaluation of the potential for the energy recovery of the selected species were carried out. It was observed that energetic valorization (i.e., to enhance the value by planned actions) of these species is difficult because they present high levels of ash and metals, becoming prone to the occurrence of fouling and slagging phenomena. Thus, the creation of value chains that justify the incorporation of these materials becomes very difficult, except if used in non-certified, small-scale and locally based processes. The possibility of recovery through thermochemical conversion processes, such as torrefaction, pyrolysis or gasification, must be studied so that more efficient and feasible recovery alternatives can be found, allowing for the creation of value chains for these residual materials to promote their sustainable management and, thus, mitigate the risk of rural fires occurring.